2017
DOI: 10.1039/c7ra07588j
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric wettable chitosan–silk fibroin composite dressing with fixed silver nanoparticles for infected wound repair: in vitro and in vivo evaluation

Abstract: The treatment of large-area infected wounds remains a significant challenge, as there is no effective wound dressing for infected wound healing applicable to clinical applications. In this study, chitosan-silk fibroin composite scaffolds containing silver nanoparticles (AgNP) that underwent asymmetric modification were fabricated for tissue engineering dressings. The scaffolds were prepared from a solution containing a chitosan-silk-fibroin emulsion with added AgNPs using a lyophilization approach and with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The water retention time of the CS/PVA and CS/PVA/Pd membrane is about 20 h (Figure 6c), which is higher than some previously reported dressing [32,33]. Effective dressing moisture retention helps to reduce clinical infections and scarring [34].…”
Section: Resultsmentioning
confidence: 93%
“…The water retention time of the CS/PVA and CS/PVA/Pd membrane is about 20 h (Figure 6c), which is higher than some previously reported dressing [32,33]. Effective dressing moisture retention helps to reduce clinical infections and scarring [34].…”
Section: Resultsmentioning
confidence: 93%
“…Such a composite can be considered as wound dressing and tendon reconstruction material in future. Chitosan-silk fibroin composite scaffolds containing silver nanoparticles (AgNPs) were fabricated for tissue engineering dressings by Liu et al [ 179 ]. The materials fabricated in such a way showed good antimicrobial properties and can thus be considered for application in wound dressing.…”
Section: Composites Based On Chitosan Silk Fibroin and Inorganic Part...mentioning
confidence: 99%
“…Asymmetric membrane was an emerging functional dressing since they can mimic construction of skin and furnish the compatible environment for wound healing 10 . Asymmetric membranes have a compact outer layer which similar to skin epidermis, exhibit hydrophobicity that could inhibit the adhesion of the bacteria and prevent the loss of water 1 . Moreover, the hydrophilic inner layer played the role of skin dermis, which could provide an ideal microenvironment of wound healing, and further promote delivery of nutrition and remove the excess exudates 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infection of a skin wound was the main reason of delayed wound healing, and high bacterial levels will hinder the progression of wound healing. 1 Unfortunately, prior study reported that infection caused by antimicrobial-resistant pathogens may lead to 10 million annual deaths by the year 2050. 2 Bacterial infection was usually accompanied by inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation